No evidence for myocarditis or other organ affection by induction of an immune response against critical SARS-CoV-2 protein epitopes in a mouse model susceptible for autoimmunity - Ignatz, Rebecca M.; Zirkenbach, Vanessa A.; Kaya, Mansur; Stroikova, Vera; Öttl, Renate; Frey, Norbert; Kaya, Ziya (International journal of molecular sciences, 2023)
After Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) developed into a global pandemic, not only the infection itself but also several immune-mediated side effects led to additional consequences. Immune reactions such as epitope spreading and cross-reactivity may also play a role in the development of long-COVID, although the exact pathomechanisms have not yet been elucidated. Infection with SARS-CoV-2 can not only cause direct damage to the lungs but can also lead to secondary indirect organ damage (e.g., myocardial involvement), which is often associated with high mortality. To investigate whether an immune reaction against the viral peptides can lead to organ affection, a mouse strain known to be susceptible to the development of autoimmune diseases, such as experimental autoimmune myocarditis (EAM), was used. First, the mice were immunized with single or pooled peptide sequences of the virus’s spike (SP), membrane (MP), nucleocapsid (NP), and envelope protein (EP), then the heart and other organs such as the liver, kidney, lung, intestine, and muscle were examined for signs of inflammation or other damage. Our results showed no significant inflammation or signs of pathology in any of these organs as a result of the immunization with these different viral protein sequences. In summary, immunization with different SARS-CoV-2 spike-, membrane-, nucleocapsid-, and envelope-protein peptides does not significantly affect the heart or other organ systems adversely, even when using a highly susceptible mouse strain for experimental autoimmune diseases. This suggests that inducing an immune reaction against these peptides of the SARS-CoV-2 virus alone is not sufficient to cause inflammation and/or dysfunction of the myocardium or other studied organs.